THE ROLE OF SOCIAL STUDIES EDUCATION IN BUILDING SOCIAL AWARENESS IN GENERATION Z - Torkis Dalimunte (CV. Asry Persada Quality, 2025)
In today's era, various influences permeate various areas of life. These influences cause various social problems, such as individualism, selfishness, lack of effective communication, low empathy, lack of responsibility, low discipline, and lack of cooperation and interaction in community life. Social studies play an important role in developing students' social skills. Acquiring social skills will enable students to live more functionally and meaningfully in the era of globalization. In this context, social studies education aims to form individuals who not only understand social, economic, and cultural phenomena, but are also able to internalize the values of togetherness, justice, and social responsibility. Social studies education also emphasizes the importance of digital and media literacy, so that Generation Z can sort out credible information, avoid hoaxes, and develop an inclusive view of differences. Thus, social studies education not only provides conceptual knowledge, but also instills awareness to act as agents of change who are adaptive to social challenges and are able to collaborate in building a sustainable society. The role of effective social studies education will create a young generation that is empathetic, has high social awareness, and contributes significantly to creating positive change in society.